Painful Rib Syndrome a Series of 89 Cases (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Painful rib syndrome is an under diagnosed or neglected clinical entity presented with pain in the lower chest and upper abdomen with a tender spot (or spots) at the lower costal margin. This study was designed to see the presentation of a relatively less recognized clinical condition painful rib syndrome. Consecutive patients presenting with pain in the lower chest or upper abdomen at one or both sides with reproducible tender points or points on the costal margin and positive hooking sign were included. Patients’ epidemiological and clinical data were recorded. A routine x-ray chest of PA view and ultrasonogram of the abdomen were done in all. Data analysis was done using SPSS (Statistical Package for Social Science) version 20. Total 89 patients, male 31(34.8%) and female 58(65.2%) with age ranging from 10 to 70 years (mean 35.34) were included. Of them, 48(53.9%) were within 26 to 45 years group, 43(48.3%) were housewives and 47 (52.8%) were from middle-class economic group. Among them, 16 (18%), 16 (18%), 12 (13.48%), and 30 (33.71%) patients presented with pain in the right lower chest, left lower chest, both sides of chest and right upper abdomen respectively and were managed conservatively with complete or acceptable improvement in 78(87.64%) patients. Painful rib syndrome can be diagnosed easily by history, clinical examination, and minimum investigations which may save patients from anxiety and economic loss.Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(1): 29-32